Institutional quality and government efficiency - Alberto Chong; Mark Gradstein (Inter-American Development Bank, Research Department, 2007)
Poorer countries have a much smaller public sector and correspondingly a smaller tax burden than richer countries, yet, their economic performance has not been necessarily better. Using a simple model, this paper suggests that the growth and welfare effects of taxation are mediated through institutional quality; consequently, optimal tax levels increase with improved institutional quality. The paper then employs firm-level perceptions on the quality of public services and on the tax burden to test some of the model's predictions. Consistent with these predictions, the paper finds that a higher level of institutional quality bolsters positive perceptions of the quality of public services while at the same time moderating the view of taxes as an obstacle to growth.
Keywords: H20; H41; O10; O17; 330; Institutions; Taxes; Quality of Public Services